Pola Sebaran Tumbuhan Invasif dikawasan Taman Nasional Bukit Sulap Kota Lubuklinggau - Nopa Nopiyanti; Reny Dwi Riastuti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to determine the types of invasive plants that exist and to find out the pattern of invasive plant distribution. Research results obtained from 8 plots found 35 species from 25 invasive plant families, random invasive plant distribution patterns, namely in Phyllanthus urinaria (Meniran), Graptophyllum pictum L (Purple Leaf), Nephrolepis biserrata (Sword Spikes), Elais guneensis J (Sawit ), Baccaureamotleyana (Rambe), Cassia Alata (Chinese Ketepeng), Acacia auricuformis (acacia), Alpinia maccensis (galangal forest), Paraserianthes falcataria (Sengon), Clibadium surinamense (Clibadium), Gynura divaricata (Leaf of god), Urena lobal (Pulutan lobus) ), Piper aduncum (Sirihan), Setaria sphacelata (Setaria grass), Asplenium nidus (Bird's nest nails), Averhoa carambola.L (Star fruit), Artocarpus heterophyllus (Jackfruit). Conclusion, the highest level of spread pattern of invasive plants is Calamus rotang (Rattan), Chromolaena odorata (left leaf nyuh), Diplazium esculentum s (Fern), Talipariti tiliaceum (Waru) of -0.14. The lowest uniform pattern of invasive plant spread is Cenchrus purpureus (elephant grass) at -5.86. Keywords: sulap Hill, invasive, distribution pattern, Plants